The Feasibility of an eLearning Nutrition Education Program for Low-Income Individuals. Issue 1 (January 2017) - Stotz, Sarah; Lee, Jung Sun; Rong, Hui; Murray, Deborah
Background. Online eLearning may be an innovative, efficient, and cost-effective method of providing nutrition education to a diverse low-income audience. Aims. The intent of this project is to examine perceptions of nutrition educators regarding the feasibility of an eLearning nutrition education program tailored to low-income Georgians. Method. Semistructured individual interviews were conducted, guided by the constructivist theory. The interview guide focused on three themes: accessibility, literacy, and content. A prototype of the program also served as a talking point. Interviews were conducted in two urban Georgian counties in a location chosen by each participant. We recruited a convenience sample of Georgian nutrition educators ( n = 10, 100% female, 50% Black). Interviews were transcribed and analyzed using constant comparative method. Results and Discussion. Motivation is considered the primary barrier to program feasibility. Neither access to the Internet nor literacy are considered significant barriers. Inclusion of skill-based, visual education methods such as cooking videos, recipes, and step-by-step teaching tools was highlighted. Nutrition educators perceived this program would be a feasible form of nutrition education for the priority audience. Conclusions. Findings from this study will inform the user-centered development of the program.